Hubungan Influencer Marketing Terhadap Kepercayaan Konsumen Dengan Keputusan Pembelian Produk Kecantikan Sebagai Variabel Moderasi - Yandri Toar (Jurnal Manajerial, 2025)
Background – The rapid growth of social media, particularly Instagram, has revolutionized the way consumers interact with brands. With the increasing skepticism toward traditional advertising, influencer marketing has emerged as a more personal and trusted method of communication. In the beauty industry, where consumer trust is paramount, influencers play a crucial role in shaping purchase behavior through their perceived authenticity and expertise. This shift in consumer behavior and marketing strategy highlights the need to understand how influencer marketing influences consumer trust and purchase decisions. Aim – This study aims to examine the influence of influencer marketing on consumer trust and analyze whether purchase decision acts as a moderating variable in the relationship between influencer marketing and consumer trust in the context of beauty products. Design / methodology / approach – This quantitative study employs a moderation regression analysis using the Partial Least Square (PLS) method. The sample consists of 100 respondents who are users of beauty products and followers of beauty influencers on Instagram. Data were collected through online questionnaires using a Likert scale (1 to 5). The study evaluates the validity, reliability, R² values, and hypothesis testing using SmartPLS software. Findings – The results reveal that influencer marketing significantly affects both purchase decisions and consumer trust. Additionally, purchase decisions positively contribute to the development of consumer trust. However, the role of purchase decision as a moderating variable in the relationship between influencer marketing and trust is not statistically significant. These findings are consistent with prior research emphasizing the importance of influencer credibility and emotional connection in driving consumer trust and behavioral intention. Conclusion – Influencer marketing is a powerful tool in building consumer trust and influencing purchase decisions, especially in the beauty product sector. While purchase decisions enhance trust, their moderating effect is limited. Effective influencer marketing strategies require not only reach and popularity but also authenticity and consistent positive consumer experiences. Research implication – The findings provide practical implications for marketers in the beauty industry to prioritize influencer selection based on credibility and trustworthiness. This research also contributes to the growing literature on digital marketing strategies, offering insights into how trust mediates consumer behavior in social commerce. Limitations – This study is limited to Instagram users in Indonesia and focuses solely on beauty product consumers. Future research could expand the sample size, include other social media platforms, or explore different demographic segments to enhance generalizability.